The Relationship Between Sugar-Sweetened Beverages, Takeaway Dietary Pattern, and Psychological and Behavioral Problems Among Children and Adolescents in China - Zhang, Yi; Wu, Xiaoyan; Wang, Qianling; Zong, Qiao; Wang, Renjie; Li, Tingting; Tao, Shuman; Tao, Fangbiao (Frontiers in Psychiatry, 2021)
Background and Aim: The association of sugar-sweetened beverages (SSBs) consumption and takeaway dietary pattern with psychological problems in Chinese children and adolescents have not been concretely reported. Our study aimed to investigate the association between SSBs consumption, takeaway dietary pattern and psychological and behavioral problems (PBPs). Methods: Cluster sampling method has been adopted from April to May 2019 to conduct a questionnaire survey among 30,188 children and adolescents in grade 1 to 12 from 14 schools in 6 streets in Bao’an District of Shenzhen. This cross-sectional study investigated the association of consumption of SSBs and takeaway patterns with PBPs, PBPs measured by the Strengths and Difficulties Questionnaire (SDQ) in primary, junior, and senior high school students, respectively. Results: A total of 33 801 primary, junior and senior high school students (mean age=12.44, SD=3.47) ranging from 6 to 18 years old were recruited in this study using a health survey of children and adolescents in junior and senior high schools (Grades 1–12), and 30,188 students with no missing data were finally analyzed (questionnaires with missing value >5% were excluded). The top three sugar-sweetened beverages in the intake frequency were milk beverages drinks (not milk), vegetable protein drinks, fruit and vegetable juice drinks. Adjusted for demographic factors, the higher frequency of students consuming SSBs who have significantly higher PBPs, the higher frequency of students consuming takeaway dietary patterns who also has significantly higher PBPs. More frequent intake of SSBs and higher takeaway dietary patterns were associated with higher SDQ total difficulties scores. Compared with low and medium consumption of SSB, children and adolescents who have high SSBs intake were more associated with total difficulties score, and compared with low and medium takeaway dietary patterns, children and adolescents who have high takeaway dietary patterns were more associated with total difficulties score. The joint associations of SSBs and take away pattern with SDQ were stronger than the associations individually. Conclusions: Students consuming higher SSBs and take away dietary pattern associated with increased levels of PBPs individually and interactively. These results may have implications for mental health prevention in adolescents.